Occurrence of carbapenem multidrug-resistant Pseudomonas aeruginosa carrying blaVIM metallo-ß-lactamases and their biofilm phenotypes in Al-Azhar University Hospital - Rehab Mousa, Magdy F. El-Kady, Asmaa A. A. Hussein, Amr E. Ahmed, Ahmed Osama El-Gendy (Journal of Applied Pharmaceutical Science, 2022)
Pseudomonas aeruginosa are quite a common cause of hospital-acquired infections. The goal of this study was to characterize P. aeruginosa isolates and identify the prevalence rate of P. aeruginosa resistant to imipenem due to metallo-ßlactamase (MBL) genes. A total of 74 P. aeruginosa isolates were obtained between November 2015 and April 2017 from Al-Azhar University Hospital, Assiut, Egypt. The disk diffusion method was applied to determine antimicrobial resistance patterns according to the Clinical and Laboratory Standards Institute, and the microtiter plate assay was managed to explore the biofilm formation. The MBL genes, blaIMP and blaVIM, were finally identified using the polymerase chain reaction (PCR) within imipenem-resistant strains. The rate of resistance to imipenem was 36.5%, and the rates of resistance for P. aeruginosa to carbenicillin, gentamicin, ciprofloxacin, ceftazidime, levofloxacin, and amikacin were 94.6%, 70.3%, 68.9%, 66.2%, 62.2%, and 58.1%, respectively. About 69% of the strains were MDR, and 86.27% of the multi-drug resistant (MDR) strains were biofilm producers. PCR showed that eight strains of imipenem-resistant P. aeruginosa contained blaVIM, while blaIMP gene was not detected. Possession of nosocomial multi-drug resistant P. aeruginosa infections was significantly associated with past antibiotic therapy or catheterization (p < 0.05). Moreover, this study demonstrates that the degrees of antibiotic resistance and biofilm production are directly linked. Ongoing antimicrobial susceptibility testing and antibiotic prescription surveillance are critical for enhancing antimicrobial stewardship measures. Additionally, further transmission of nosocomial diseases must be prevented by infection control method.
Keywords: Hospital, infection, metalloß-lactamases, nosocomial, Pseudomonas aeruginosa